(untitled) (Contemporary Journal of Social Science Review, 2025)
Muhammad Hanif’s novel Our Lady of Alice Bhatti (2011) offers a heartbreaking depiction of Karachi, a cosmopolitan city with its necropolitical environment where life and death are governed politically. This article provides a comprehensive and critical approach by merging the materialist perspective of Social Reproduction Theory (SRT) which is a significant progress in modern Marxist Feminism with the complex framework of intersectionality. The protagonist of the novel, ‘Alice Bhatti’ travels through a tragic trajectory, who is a catholic nurse by profession from ‘Churah’ origin. She has been employed as a junior nurse. The novel illustrates that capitalist exploitation is inherently influenced and aggravated by patriarchal, religious and caste-based oppressions. The article establishes firstly, the theoretical importance of this synthesis then examines how the protagonist of the novel, Alice’s paid and unpaid labor is exploited with intersecting lines and finally delves in the novel’s portrayal of systemic violence as the ultimate manifestation of this dialectic. Muhammad Hanif has not simply depicted the class struggle in the novel, rather outlined a ‘dialectic of social reproduction and identity’ in which the marginalized status of Alice’s renders both a saint to the downtrodden and a disposable body for the state machinery. Her existence and sorrowful demise shed light on what Achille Mbembe (2023) denotes as ‘the subjugation of life to the power of death’.